The Motivational Outcomes of Psychological Need Support among Pre-Service Teachers: Multicultural and Self-determination Theory Perspectives - Kaplan, Haya; Madjar, Nir (Frontiers in Education, 2017)
The study employed a Self-Determination Theory (SDT) framework to explore pre-service teachers’ perceptions of their professional training in relation to motivational outcomes. We hypothesized that students’ perceptions of basic psychological need support will be positively associated with their sense of relatedness, competence, and autonomous motivation, and negatively associated with controlled motivation. Sense of relatedness, competence, and autonomous motivation were hypothesized to be positively associated with personal accomplishment, engagement, and self-exploration, and negatively associated with emotional exhaustion. The study was conducted within a multicultural context, which enabled exploration of the hypotheses among students from two different cultural backgrounds. Based on the universality of SDT we expected that the general models would be similar for both cultures, although some mean-level and correlational paths may be different. The sample (N = 308; mean age 23.4) consisted of Muslim-Arab Bedouin (55.3%) and Jewish (44.7%) pre-service teachers enrolled in the same teachers’ college in Israel. The participants completed self-report surveys assessing their sense of basic psychological need support, autonomous and controlled motivation, self-accomplishment, engagement, self-exploration, and emotional exhaustion. Multiple-group structural equation modeling revealed that need support contributed positively to autonomous motivation, sense of relatedness, and sense of competence in both cultures. Autonomous motivation contributed positively to sense of self-accomplishment, engagement, and self-exploration. Competence in turn was positively related to engagement and negatively related to emotional exhaustion, and relatedness was associated with engagement only among the Bedouin students, and with self-accomplishment only among the Jewish students. These results indicate that sense of need support is highly important regardless of cultural background, while sense of relatedness may be related to different outcomes across cultures. The findings demonstrate the utility of Self-Determination Theory within the context of multicultural teacher training and support the universality of the theoretical framework.